1992
DOI: 10.1148/radiology.183.1.1549668
|View full text |Cite
|
Sign up to set email alerts
|

Coaxial transthoracic fine-needle biopsy in patients with a history of malignant lymphoma.

Abstract: Efficacy and safety of coaxial transthoracic fine-needle biopsy were evaluated in 54 patients with a history of malignant lymphoma and new chest lesions. Twenty-one patients had recurrent lymphoma. Correct diagnosis was made in 17 of the 21 patients (81%) after one biopsy. The sensitivity increased to 95% with repeat needle biopsy in three patients. Immunophenotyping (determining phenotype by means of immunologic examination) was essential for a definitive diagnosis of lymphoma in three patients. Non-lymphomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…In this setting we find FC preferable to immunohistochemistry, which is subject to more staining artifact and subjective interpretation. 7,27,28,41 This study confirmed the findings of previous studies 4,10,26,30,37,40 showing a high level of diagnostic accuracy (82%) when using FNAB with adjuvant FC. The addition of core biopsy to FNAB increased the diagnostic accuracy to 93% in our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this setting we find FC preferable to immunohistochemistry, which is subject to more staining artifact and subjective interpretation. 7,27,28,41 This study confirmed the findings of previous studies 4,10,26,30,37,40 showing a high level of diagnostic accuracy (82%) when using FNAB with adjuvant FC. The addition of core biopsy to FNAB increased the diagnostic accuracy to 93% in our study.…”
Section: Discussionsupporting
confidence: 89%
“…FNAB, 4,5,10,16,26,30,34,37,40 while others prefer core biopsies obtained by larger needles. 3,8,9,11,13,18,21,24,25,32,36,42,43 Silverman et al compared the results of core biopsies and FNABs and determined that fine needles are as likely as larger needles to obtain diagnostic material.…”
mentioning
confidence: 99%
“…Biopsy was considered in order to discriminate between the infectious and immunological nature of the disorder. Indeed, there is evidence in the literature that transthoracic needle biopsy can provide or suggest diagnosis of infectious (opportunistic, bacterial) or immunological diseases (hypersensitivity pneumonitis, pulmonary haemorrhage, eosinophilic lung disease) [19,20].Coagulation studies, including prothrombin time, partial thromboplastin time and platelet count, performed the day before the biopsy, were normal. Percutaneous biopsy was performed under CT guidance with a 20-gauge Chiba-type needle.…”
mentioning
confidence: 99%
“…Its sensitivity is reported to be 81 % and is increased to 95% with repeat biopsies in a series of 54 patients with a history of malignant lymphoma. 4 In our experience, needle biopsy proved its value in cases with multiple nodules or nodules with a diameter of 1 em or more. In these cases, the underlying disease is often a more "malignant" one, such as PTLD or abscesses (bacterial or fungal) , where a prompt histologic or cultural diagnosis enables immediate therapy and may thus improve the survival rates of L Tx recipients.…”
Section: Patientmentioning
confidence: 69%
“…In the two last patients, spiral CT with 8-mm-thick sections was used (Somatom Plus-S, Siemens; Erlangen, Germany). The CT-guided-fine-needle biopsies were performed as described elsewhere 4 From each nodule, about five specimens were taken by using the 18-to 22-gauge (Autovac, Angiomed; Karlsruhe, Germany) or a needle system (Surecut TSK; Tokyo, Japan). Biopsy specimens were fixed in 7.5% buffered formaldehyde solution (Formalin), embedded in paraffin, and sectioned serially at 4 J.I.ID.…”
Section: Follow-upmentioning
confidence: 99%